Reduction of Image Artifacts in Mice by Bladder Flushing with a Novel Double-Lumen Urethral Catheter - Chad R. Haney; Adrian D. Parasca; Kazuhiro Ichikawa; Benjamin B. Williams; Martyna Elas; Charles A. Pelizzari; Howard J. Halpern (Molecular Imaging)
In electron paramagnetic resonance imaging (EPRI), the accumulation of contrast agent in the bladder can create a very large source of signal, often far greater than that of the organ of interest. Mouse model images have become increasingly important in preclinical testing. To minimize bladder accumulation on mouse images, we developed a novel, minimally invasive, MRI/EPRI-friendly procedure for flushing a female mouse bladder. It is also applicable to other imaging techniques, for example, PET, SPECT, etc., where contrast agent accumulation in the bladder is also undesirable. A double-lumen urethral catheter was developed, using a standard IV catheter with a silicone tube extension, having a polyethylene tube threaded into the IV catheter. Flushing of the bladder provides a substantial reduction in artifacts, as shown in images of tumors in mice.